Formação Ética na Educação Profissional, Científica e Tecnológica - Nunes, Vinícius Bozzano; Souza, Leonardo Lemos De (Universidade Federal do Rio Grande do Sul - Faculdade de Educação, 2018)
Abstract: The mismatch between technological development and human development is evident in the Federal Network of Professional, Scientific and Technological Education, making ethical formation an important point of discussion in this context. This article shows results of research that investigates how this education is represented in the speech of the pedagogical managers of the Network. From the data, the emphasis is on disciplinary approaches and professional or professionalizing representations of business and neoliberal ethics. It is concluded that the morality theme should integrate the debates about Professional Education, reconciling the technical and human dimensions of formation and thus guiding the educational process toward emancipatory.

Resumo: O descompasso entre desenvolvimento tecnológico e desenvolvimento humano é evidente na Rede Federal de Educação Profissional, Científica e Tecnológica, fazendo da formação ética um importante ponto de discussão nesse contexto. Este artigo traz resultados de pesquisa que investigou como essa formação está representada na fala dos gestores pedagógicos da Rede. Dos dados, destacam-se a tônica nas abordagens disciplinares e as representações profissionais ou profissionalizantes da ética empresarial e neoliberal. Conclui-se que o tema moralidade deve integrar os debates sobre a Educação Profissional, reconciliando as dimensões técnica e humana da formação e assim orientando o processo educativo em direção emancipatória.
Ethical Formation in Professional, Scientific and Technological Education
Keywords: Professional, Scientific and Technological Education; Ethical Education; Moral Education; Barbarism; Representations; Educação Profissional, Científica e Tecnológica; Formação Ética; Educação Moral; Barbárie; Representações